DEVELOPMENT OF INTERACTIVE MULTIMEDIA LEARNING MATHEMATICS LEARNING MEDIA USING ADOBE FLASH CS6 - Zafrullah Zafrullah; Zetriuslita Zetriuslita; Sri Rezeki; Suripah Suripah (UIR PRESS, 2024)
Ongoing advancements have profoundly reshaped the development of educational media, with validity being a pivotal factor in creating high-quality products, representing a critical phase in their development. In essence, validity holds a key position in the production of superior educational materials. The primary objective of this study is to design and assess the validity of interactive multimedia-based mathematics learning tools using Adobe Flash CS6. This research belongs to the category of Research and Development (R&D) or developmental research. The methodology adopted for this developmental research follows a modified Plomp procedure, involving three of its five stages: the initial investigation phase, the development phase or prototyping, and the assessment phase. To gauge the validity of the media, the research employs a validation sheet as the data collection instrument. The analysis process entails scoring based on assessments made by the validator. The outcomes of the validation testing indicate that the media is deemed highly valid, achieving an impressive validation rate of 90.59%. The media is now deemed ready for use with only minor revisions required. One notable advantage of this learning media is its compact size, ensuring compatibility with all computer types, including those with low specifications.